Pengaruh krom pada elektrodeposisi nikel dari larutan nikel-krom - Pramujo Widiatmoko; Isdiriayani Nurdin (Jurnal Teknik Kimia Indonesia, 2011)
The chromium effect on nickel electrodeposition from nickel-chromium solution Electrodeposition, which can convert nickel ion into pure nickel metal, is an alternative for reducing nickel concentration in electroplating waste and in same time increasing its economic value. The aim of this research is to study the effect of chromium presence on the performance of Nickel recovery from liquid waste of Ni-Cr electroplating process. Liquid of electroplating waste leachate is represented by solutions containing nickel and chromium sulfate method. All experiments were carried out at ambient temperature and pressure with Cr/Ni ratio and boric acid composition as variables. Result of the research shows that chromium presence in solution with 28.9% Cr/Ni ratio increases activation polarization of about 500 mV. Optimum condition of the experiment is obtained for Cr/Ni ratio 3.7%-w. Increasing Cr/Ni ratio from 3.7% to 14.8% decreases current efficiency by 57% and deposition efficiency by 5%, and also increases energy consumption by 8.3%. Morphology of deposited nickel deteriorates with increasing of Cr/Ni ratio and hydroxide compound is formed when it reaches 14.8%. Keywords: nickel electrodeposition, nickel-chromium solution, chromium, electroplating wasteAbstrakElektrodeposisi merupakan metode alternatif yang potensial untuk mengurangi kandungan nikel dari limbah elektroplating sekaligus meningkatkan nilai ekonomisnya, dengan produk berupa logam nikel murni. Penelitian ini bertujuan mengkuantifikasi pengaruh krom dalam proses pemulihan nikel dari larutan limbah industri yang mengandung nikel dan krom. Nikel sulfat dan krom sulfat digunakan sebagai pendekatan larutan hasil ekstraksi limbah padat. Percobaan dilakukan pada tekanan dan temperatur ruang dengan variasi rasio krom terhadap nikel serta konsentrasi asam borat sebagai aditif. Hasil percobaan menunjukkan bahwa keberadaan krom dengan rasio Cr/Ni 28,9% meningkatkan polarisasi aktivasi sekitar 500 mV. Kondisi optimum untuk percobaan ini diperoleh ketika rasio Cr/Ni 3,7%-berat. Perubahan rasio Cr/Ni dalam larutan dari 3,7% menjadi 14,8% menurunkan efisiensi arus sebesar 57%, menurunkan efisiensi deposisi 5%, serta meningkatkan kebutuhan energi hingga 8,3%. Morfologi deposit nikel menjadi lebih buruk dengan kenaikan rasio Cr/Ni, dan berubah menjadi deposit hidroksida pada rasio Cr/Ni 14,8%.Kata kunci: elektrodeposisi nikel, larutan nikel-krom, krom, limbah elektroplating